The Correlation of Video Games with Positive Affect and Negative Affect Among UTAR (Perak Campus) Undergraduate Students - Lim, Yong Quan; Cheong, Hui Qi; Saw, Shi Qi (2016)
Video games are becoming increasingly popular especially among students. There are also recent tragedies involving students who might have issues with psychological wellbeing. Since video games are popular among students and students are vulnerable to various emotions, this study aimed to assess the correlation of hours spent on video games and student’s positive and negative affect. It was hypothesised that hours spent on video games is correlated with both positive and negative affect. 300 UTAR-PK students were recruited in this study. The participants were asked to report their total hours spent on video games in the past four weeks and assessed with SPANE (Diener et al., 2009) for their positive and negative affect. The result indicated that hours spent on video games has a statistically significant positive correlation with positive affect of students but no significant correlation with negative affect. Implications and limitations of this study were discussed and recommendations for future studies were made.